Pengolahan Sampah Organik Sebagai Upaya Peningkatan Ketahanan Iklim Masyarakat - Nike Triwahyuningsih; Amrina Yasmine Shafira; Tati Budi Kusmiyarti (Yayasan Literasi Sains Indonesia, 2025)
Community empowerment activities aimed at enhancing the knowledge and skills of the community in managing and processing household organic waste have been conducted in Notoprajan Village, Yogyakarta City. The target of this activity is the PKK members and community groups in the village. The activity was conducted using extension and education methods on waste management, which included waste reduction and handling, followed by practical training on processing organic waste. Through this activity, products have been produced in the form of Ecoenzyme scrub, used cooking oil candles, gkalranulated compost, pasteurized liquid organic fertilizer, tutorial videos, and publications in national journals. It is concluded that this training activity can enhance the knowledge and skills of the residents of Kalurahan Notoprajan in managing and processing organic waste. The impact of the success of this activity is contributing to the direct reduction of organic waste volume, minimizing methane (CH4) production and other greenhouse gas emissions, supporting climate change mitigation efforts at the community level, providing practical skills that can open new economic opportunities for the community, transforming waste into sellable products, and enhancing financial independence, as well as improving climate resilience through increased environmental awareness, independence, and active community participation in maintaining the cleanliness and health of their own environment